IMPLEMENTASI PRINSIP GESTALT PADA PERANCANGAN MOTIF TEKSTIL TERINSPIRASI DARI TOKOH DEWI WARA SRIKANDI: IMPLEMENTATION OF GESTALT PRINCIPLES IN DESIGNING TEXTILE MOTIFS INSPIRED BY THE FIGURE OF DEWI WARA SRIKANDI - Fabio Ricardo Toreh; Krishna Hutama; Yan Yan Sunarya (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Implementation Of Gestalt Principles In Designing Textile Motifs Inspired By The Figure Of Dewi Wara Srikandi. In the era of today's modern world, there are many western film worlds that carry heroic stories from figures, such as Superman, Wonder Woman, Spiderman and many more. It is because of this that these western world heroic figures have become popular, especially among today's younger generation, which in the end have been used as inspiration for goods for daily needs into fashion products. Because of this, the author had the idea to make fashion products that brought back local cultural values ​​originating from the story of patriotism in the Indonesian Wayang Purwa world. Apart from that, there are also many heroic stories that are often forgotten by today's millennials, which still have the essence of teaching the values ​​of norms and there is an eastern Indonesian nation. One of the characters who has characteristics and a patriotic attitude that deserves to be reappointed is the figure of Dewi Wara Srikandi. Likewise, to be able to take part in the preservation of Wayang culture as a heritage of world masterpieces in the form of a shadow puppet show with original speech from Indonesian culture and has been crowned by UNESCO in 2003. By bringing up stories from the figure of Dewi Wara Srikandi, the writer hoped to rejuvenate Indonesian wayang stories and accept the essential values ​​and cultural characteristics embedded in the stories related to these characters and pass on the values ​​contained in them to the next generation. This research is also expected to produce an innovative textile motif by implementing Gestalt theory as the foundation of the creative idea through the arrangement of motifs, colors, and proportions of visual elements, while still preserving key principles of the Wayang Purwa culture, which is rich in and closely tied to Indonesian cultural identity. The creation of motif designs refers to the principles of Gestalt theory and is implemented in the form of fashion design that incorporates the essential anatomy of clothing creation—while maintaining comfort and wearability for special occasions as key elements. The method involves literature studies and structured in-depth interviews with expert panelists to explore the essence, characteristics, and cultural values embodied in the story of the character Dewi Wara Srikandi. The outcome is a conceptual design of textile motifs inspired by this figure.